Competition from Low-Wage Countries and the Decline of Corporate Tax Rates: Evidence from European Integration - Overesch, Michael; Rincke, Johannes (World Economy, 2009)
We exploit the rapid economic integration of Eastern and Western Europe after 1989 as a natural experiment to assess the effect of international competition for mobile capital on corporate tax rates. By means of a series of difference-in-difference estimations, we show that Western European countries which have been directly exposed to neighbours in Eastern Europe have reacted to the intensified competition by cutting their corporate tax rates by 8.1 to 10.5 percentage points relative to those countries which do not share a common border with countries in Eastern Europe. It seems that this effect has mainly worked through Eastern European countries offering lower wages and less through competition over corporate tax rates.
WiSo-Import:2015-03-26:1708
Keywords: tax competition; low-wage countries; corporate taxes